Patients and caregivers costs for colonoscopy-based colorectal cancer screening: Experience of low-income individuals undergoing free colonoscopies. (June 2017) - Hoover, Sonja; Subramanian, Sujha; Tangka, Florence K.L.; Cole-Beebe, Maggie; Sun, Amy; Kramer, Cheryl L.; Pacillio, Gina
Highlights: We surveyed patients about direct and indirect medical costs of free colonoscopies. There are costs associated with free colonoscopies in terms of time and travel. Costs related to time and travel may be potential barriers to colonoscopies. Abstract: Many studies have documented barriers to colorectal cancer screenings. However, there is lack of comprehensive information on the time and costs borne by low-income patients and the persons accompanying the patient (caregiver) for colonoscopies in the United States. We surveyed patients in three health clinics in Philadelphia retrospectively who had undergone free colonoscopies in the previous 18-month period. Participants were asked questions about time and out-of-pockets expenses for themselves and their caregivers. Even when colonoscopies were free to the patient through Colorectal Cancer Control Program funded by the Centers for Disease Control and Prevention, the patient and caregivers still incurred costs in relation to preparing for, undergoing, and recovering from a colonoscopy. These costs can be substantial and may account for some of the low colorectal cancer screening rates especially among the low-income populations. Patients' and caregivers' costs need to be considered when designing and implementing colorectal cancer control programs.